Eliciting unknown unknowns with prototypes: Introducing prototrials and prototrial-driven cultures. (March 2017) - Jensen, Matilde B.; Elverum, Christer W.; Steinert, Martin
Abstract : This paper maps and describes how prototypes are used to elicit requirements of unknown unknowns in industry. Eight engineering design companies serve as a dataset for a multi-case investigation. By semi-quantitatively analysing 19 prototypes in terms of functionality, timing, stakeholder involvement and requirement elicitation, we present a wide spectrum of prototype utilizations. However, this broad span leads to misunderstandings of what the term 'prototype' encompasses, hindering exploitation of its full potential. Hence, we introduce the term 'prototrial' that covers functional prototypes utilized in the early stages of the design process, prototypes that effectively elicit unknown unknowns. With this contribution, we encourage introducing mind-sets and behaviours that aim at exploration and learning rather than lean implementation – a prototrial-driven culture. Highlights: We map the current use of prototypes in 8 different companies. Prototypes can be used to elicit unknown unknowns throughout the design process. High functional prototypes built early in the process are especially useful to identify a wide range of unknown unknowns. We propose a new term, 'prototrial' and 'prototrial-driven cultures' to describe this specific prototype use.